LINKING HALAL INDUSTRY TO SUSTAINABLE DEVELOPMENT GOALS - Ramdani, Ramdani; Munir, Maryam Bte Badrul; Kurniawan, Taufiq; Fahmi, Moh Farih; Suryaningsih, Sri Abidah; Musafak, Moh. (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 11 No 1 (2025): The 11th International Conference of Islamic Economics and Business (ICONIES 2025), 2025)
This study examines the intersection between the Halal industry and the United Nations’ Sustainable Development Goals (SDGs), highlighting the sector’s potential to advance global sustainability agendas. Employing literature review of recent scholarly works, the paper synthesizes insights across Halal tourism, gastronomy, logistics, certification, and supply chain management. Findings reveal that Halal practices—anchored in the principles of Halal and Tayyiban—not only ensure religious compliance but also contribute to responsible consumption (SDG 12), public health and well-being (SDG 3), and inclusive economic growth (SDG 8). Empirical evidence underscores the role of Halal industries in fostering local economic resilience, generating employment, reducing waste, and strengthening cultural identity. At the same time, challenges persist, particularly in certification processes, regulatory fragmentation, and the capacity of micro- and small enterprises (MSEs) to meet compliance standards. Emerging technologies such as blockchain, IoT, and traceability systems are identified as critical enablers for transparency and sustainability in Halal supply chains. The study concludes that the Halal sector, when supported by effective governance, Islamic finance, and multi-stakeholder collaboration, can function as a strategic driver of equitable and sustainable development. It calls for future research on integrating Halal standards with green finance, refining supply chain governance, and scaling inclusive certification models to strengthen the sector’s alignment with the 2030 SDG agenda.